Utilizing Ai-Adriven Data Analytics to Improve Learning Outcomes in Educational Psychology - Haryanto, Sri; Guilin, Xie; Jiao, Deng; Wang, Yuanyuan; Sudirman, M. Yunus (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Given the rapid advances in computing capabilities, as well as advances in more sophisticated algorithms, and greater accessibility to AI tools, AI has great potential for innovation in data analytics, such as pattern recognition, classification, clustering, and prediction. Likewise in psychology education, AI-based data analytics will be able to manage data to improve student learning outcomes well. This research was conducted with the aim of seeing how influential it is to utilize AI-based data analytics to improve learning outcomes in educational psychology. Additionally, AI can give teachers more time to concentrate on direct interactions with students and the development of more innovative and effective teaching strategies by automating administrative and assessment tasks. The method used by researchers in researching Utilizing AI-Based Data Analytics to Improve Learning Outcomes in Educational Psychology is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. The results of data acquisition will also be tested again using the SPSS application. From the research results, it can be seen that AI can accurately predict student academic performance. This can be done by analyzing various factors such as study patterns, class participation, and previous test scores. AI also allows teachers to be proactive in helping their students when they encounter a particular problem. From this research, researchers can conclude that in educational psychology, the use of AI-based data analytics has great potential to improve learning outcomes by personalizing student learning experiences such as, enabling early intervention, improving assessments, increasing operational efficiency, supporting better curriculum development, and offers a customizable learning system.